2015
DOI: 10.1093/carcin/bgv049
|View full text |Cite
|
Sign up to set email alerts
|

ERBB4 is over-expressed in human colon cancer and enhances cellular transformation

Abstract: The ERBB4 receptor tyrosine kinase promotes colonocyte survival. Herein, we tested whether ERBB4's antiapoptotic signaling promotes transformation and colorectal tumorigenesis. ERBB4 alterations in a The Cancer Genome Atlas colorectal cancer (CRC) data set stratified survival, and in a combined Moffitt Cancer Center and Vanderbilt Medical Center CRC expression data set, ERBB4 message levels were increased at all tumor stages. Similarly, western blot and immunohistochemistry on additional CRC tissue banks showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 52 publications
4
73
0
Order By: Relevance
“…43,44 Moreover, it has been considered to mediate acquired resistance to chemotherapy. 36 Consistently, we found that inhibition of ERBB4 enhanced colon cancer cells apoptosis in response to L-OHP.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Moreover, it has been considered to mediate acquired resistance to chemotherapy. 36 Consistently, we found that inhibition of ERBB4 enhanced colon cancer cells apoptosis in response to L-OHP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the overexpression or mutation of HER3 is associated with malignant cell growth, contributing to enhanced tumor progression and poor patient outcomes (8). There are potentially oncogenic ERBB4 mutations in non-small cell lung cancer (9), and it has been reported that HER4 is overexpressed in human colon cancer and enhances cellular transformation (10). In addition, HER4 promotes breast cancer cell proliferation, mediates acquired resistance to ERBB2 inhibitors and may serve as a prognostic marker in patients with breast cancer (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Besides direct EGFR signaling associated genes, the most frequent mutations observed in CRC cell lines and cases were ATM, SMAD4, KDR, ErBB4 and FBXW7, as reported by others for CRC before [57, 58]. Indeed, SMAD4, ErBB4 and FBXW7 mutations appear to confer treatment resistance to Cetuximab [5].…”
Section: Discussionmentioning
confidence: 66%